PENGARUH TAX AVOIDANCE TERHADAP COST OF DEBT PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA PERIODE 2016-2020 - Karo-Karo, Dicky Breba; Lumbangaol, Romasi (Jurnal Ilmiah Akuntansi (JIMAT), 2022)
This study aims to determine the effect of tax avoidance on the cost of debt. The population in this study are all financial statements of consumer goods industry companies listed on the Indonesia Stock Exchange in 2016-2020. The sample in this study was obtained by purposive sampling, the number of samples of 17 companies with 5 years of research obtained 85 final samples. Data collection techniques using documentation techniques. The data analysis technique used is simple linear regression and hypothesis testing using t test with a significance level of 5%. The results of the partial test (t test) show that tax avoidance has a positive and significant effect on the cost of debt, this is obtained from Tcount > T table, namely 9.438 > 1.66298. The value of R Square is 0.518, this means that 51.8% of the dependent variable can be explained by the independent variable, while the remaining 48.2% is influenced by other factors. So it can be concluded that tax avoidance has a positive and significant effect on the cost of debt.